Zmiany sekularne wysokości ciała w przemysłowym regionie Polski - Puch, Elżbieta Alicja; Jaworski, Jerzy Mirosław (Polskie Towarzystwo Antropologiczne, 1994)
SECULAR TREND OF THE BODY HEIGHT IN THE POLISH INDUSTRIAL REGION. Own data (1986) concerning the body height of 1413 children from the city of Katowice were compared with the mean values of the body height (1964,1974) from Polish anthropological literature.
SECULAR TREND OF THE BODY HEIGHT IN THE POLISH INDUSTRIAL REGION